Предмет:
АлгебраАвтор:
griffin323Автор:
maciasОтвет:
а=5; b=-4
Объяснение:
(x - a)(2x-1)(x+b) > 0
(x - a)*2(x - 0,5)(x - (-b)) > 0
(x - x1) (x - x2) (x - x3) > 0
x1 = -4
x2 = 0, 5
x3 = 5
Соответственно знакам, можно соотнести, что а=5; b=-4
Автор:
summercbtdДобавить свой ответ
Предмет:
Английский языкАвтор:
camillameltonОтветов:
Смотреть
Предмет:
ГеометрияАвтор:
robertturnerОтветов:
Смотреть
Предмет:
ИнформатикаАвтор:
damon74Ответов:
Смотреть
Предмет:
МатематикаАвтор:
sirochristensenОтветов:
Смотреть